Multiscale finite element analyses on mechanical properties of graphene-reinforced composites. Issue 20 (18th October 2019) - Guo, Zhangxin; Song, Lubin; Chai, Gin Boay; Li, Zhonggui; Li, Yongcun; Wang, Zhihua
ABSTRACT: A new multiscale simulation method for analyzing the mechanical properties of graphene-reinforced composites is proposed. The atomistic and the macroscopic scales are combined in the proposed finite element modeling approach. In the nanoscale analysis, a space frame structure of graphene is selected, the carbon atoms are described as nodes, and the carbon–carbon covalent bonds are represented with nanoscale beams. The macroscopic homogeneous isotropic model of the matrix and the interface is included in the representative volume element of the composites. The effect of graphene volume fraction and different inclined angles on the mechanical properties of the composites is investigated under axial tension. The simulation results showed that with the increase in the graphene volume fraction, the Young's modulus of the composites was increased significantly. The Young's modulus of the composites was highly dependent on the size of graphene. The stress transfer in the interface of the composites was also analyzed using this multiscale approach.